Parceria colaborativa e mentoria entre experientes e iniciantes a partir da pesquisa-formação: possibilidades de ações de indução profissional - Gomboeff, Ana Lucia Madsen (2022)
This thesis, with a qualitative approach, focuses on the pedagogical coordinator in professional insertion. This phase requires rapid learning of the profession and may generate insecurity in this professional who often faces the challenges of the position alone and with few references. This insecurity can compromise the quality of the beginner's work (GROPPO; ALMEIDA, 2013). Thus, one opted for a training research, based on the principles of action research (THIOLLENT, 2011). With formative meetings, developed by research-training, a collaborative partnership was established between university-school and between seventeen coordinators with a maximum experience of three years, 25 professors on the verge of taking up the position and the researcher, as mentor of the group. It was presupposed that collaborative partnership and mentoring, as actions of professional induction, provide reflection on the practice to the experienced and subsidies to beginners to face the setbacks of the early career. The general objective of this study was to investigate how the professional insertion of the pedagogical coordinator occurs from the collaborative partnership between experienced and beginner coordinators and from the mentoring, developed by the researcher, conceived as induction actions, and increased through research-education. The specific objectives were: a) to collectively raise, analyze and prioritize the formative needs of the research participants in order to organize and develop the formative meetings; b) identify the factors that promote the collaborative partnership between university-school and between experienced-beginners; c) to understand if and how the collaborative partnership and mentoring reverberated in the performance of the experts; d) to analyze whether and how the actions of induction of this research-training contributed so that beginners had more subsidies to face the challenges of professional insertion. The theoretical framework was based on studies of André (2012), Huberman (1995), Marcelo García (1999, 2010), Wong (2020), among other authors, who deal with induction and related concepts. Foerste (2005), Hargreaves and O'Connor (2018a, 2018b) and Passos (2016), which address collaborative actions. Antolí, Imbernón and Rodríguez (2001), Estrela e Leite (1999), who study training needs. Placco, Almeida and Souza (2015) and Placco and Souza (2006, 2018), among other scholars, who discuss coordination. The data were produced with training meetings, discussion groups, a questionnaire and WhatsApp content. Data analysis is inspired by Prose Analysis (ANDRÉ, 1983). The results revealed precariousness in public education, curtailment of teaching work, and challenges imposed by the pandemic, generating extra obstacles to the pedagogical coordinators' professional insertion. The collaborative university-school partnership made it possible to increase this partnership between experienced-beginners and the realization of mentoring, providing the experienced with a change of practice, and, for the beginners, overcoming adversity. It was concluded that collectively defining the training contents, based on the trainees' training needs, allows for the construction of mutual trust, common goals and shared commitment, favoring collaborative partnership. Experiences and doubts arising from the work context, considered material for shared reflection, provide interaction, an investigative attitude, professional collaboration and learning among equals. As for mentoring, this study indicates its benefit for mentor and stakeholders and the possibility of producing two-way collegiate mentoring